A variable time delay compensator for multivariable linear processes - Saffer, Daniel R.; Castro, Jorge J.; Doyle, Francis J. (Journal of process control, 2005)
A variable time delay compensator based on the Smith predictor is proposed. Finite difference and cinematic techniques are employed for a numerical approximation of the variable delay. The resulting multivariable controller is analyzed for robustness using the structured singular value. The technique is demonstrated through two simulated systems: a single-input, single-output numerical example, and a cross-direction paper machine control problem.